Pengaruh Bahasa Gaul Media Sosial terhadap Kemampuan Berbahasa Indonesia Mahasiswa Pendidikan Administrasi Perkantoran UNIMED : Penelitian - Ijen Fredi SetiawaBu’lolo; Nabila Khairunnisa Zahra; Naila Dewi Mutia; Nazla Aprilia; Putri Sri Lestari (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the extent to which the use of slang influences the use of Indonesian on social media among Generation Z students, particularly in the Office Administration Education Study Program at Medan State University. This study used a quantitative descriptive method with a purposive sampling technique on 50 students. The instrument was a Likert scale questionnaire to measure the intensity of slang use, the situations in which it is used, and respondents' perceptions of its influence on Indonesian use. The results showed that almost all respondents were familiar with slang terms (96%) and most used them intensively on social media (84%). Slang was predominantly used in interactions with campus friends (82%) and friends outside campus (86%), while use with family was relatively low (12%). A total of 72% of respondents stated that slang influenced their habits of using Indonesian, both in vocabulary and communication style. These findings demonstrate the dynamics of language among the younger generation, where slang functions as a social identity, but also poses challenges to the continued use of good and correct Indonesian.